Do labour market status transitions predict changes in psychological well-being?. Issue 9 (28th June 2013) - Flint, Ellen; Bartley, Mel; Shelton, Nicola; Sacker, Amanda
Abstract : Background: The objective of this study was to establish the direction of causality in the relationship between labour market status and psychological well-being by investigating how transitions between secure employment, insecure employment, unemployment, permanent sickness and other economic inactivity predict changes in psychological well-being over a 16-year period. Method: This study used data from the British Household Panel Survey (1991–2007). Psychological well-being was measured using the 12-item General Health Questionnaire (GHQ-12). Fixed effects models were utilised to investigate how transitions between labour market statuses predicted GHQ-12 score, adjusting for current labour market status and a range of covariates. Results: After taking account of the contemporaneous effects of joblessness on psychological well-being, and the impact of a range of confounding factors, experiencing a transition from employment to joblessness was significantly predictive of poorer psychological well-being. Transitions into employment were not found to have equal and opposite effects: the positive effects of moving into work from unemployment were not as large as the negative effects of job loss. Transitions between secure and insecure employment did not independently predict changes in psychological well-being. Conclusions: A causal relationship between labour market status and psychological well-being is indicated.